Optimalisasi Pemasaran Melalui Media Sosial Pada UKM Dapoer Grandma Desa Jarak Kecamatan Plosoklaten Kabupaten Kediri - Witanti, Wahyu; Arum, Willia Arum; Fitrieni, Yeni; Zahra’, Yuli Fatimatus; Widianto, Yuan Mukti; Permatasari, Vina Septiana (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This service activity aims to help UKM Dapoer Grandma, located in Distance Village, Plosoklaten District, Kediri Regency, optimize marketing via social media. Even though product marketing has been carried out online and offline, the use of social media as a promotional tool has not been maximized. To overcome this, training is provided to SME owners on effective ways to promote via social media so they can compete with other SMEs. The service method includes the stages of making pamphlets, creating content, and posting on social media. During the training, participants are taught creative techniques for maximizing product promotions. The results of the service showed a positive response from UKM Dapoer Grandma owners, as well as an increase in product sales as a direct impact of this training. Thus, this activity succeeded in increasing the understanding and skills of SME owners in using social media for marketing while strengthening the competitive position of Dapoer Grandma SMEs in the market.